SIMS U–Pb zircon geochronology of porphyry Cu–Au–(Mo) deposits in the Yangtze River Metallogenic Belt, eastern China: Magmatic response to early Cretaceous lithospheric extension - Li, X.; Li, W.; Wang, Xuan-ce; Li, Q.; Gao, Y.; Wu, Fuyuan; Liu, Y.; Tang, G. (Elsevier Science BV, 2010)
The middle-lower reaches of the Yangtze River is one of the most important metallogenic belts in China, hosting numerous Cu–Fe–Au–Mo deposits. Previous chronological and geochemical investigations mostly focused on the magmatic rocks and associated deposits in the lower reaches of the river, but the timing and genesis of the Cu–Au–(Mo) mineralized porphyries in the middle reaches are yet to be well constrained. In this study we carried out precise SIMS U–Pb zircon age determinations for a number of Cu–Au–(Mo) mineralized porphyries and barren granitoid intrusions in the Jiurui and Edong mining districts in the middle reaches of the Yangtze River valley. Our new age results reveal two discrete magmatic and mineralization events at ca. 145–146 Ma and ca. 140 Ma in the study area. The ca. 145–146 Ma granitoids signify the start of the Cretaceous magmatism in the Yangtze River Metallogenic Belt, coinciding temporally with a regional tectonic switching from a Late Jurassic transpressive tectonic regime to an earliest Cretaceous extensional regime in eastern China.